Toxoplasma Gondii Stimulates The Behavioural Changes of Rodents: Updated Evidence - Che Omar, Siti Shafiyyah; Mohd Moklas, Mohamad Aris; Mohtarrudin, Norhafizah; Osman, Malina (Journal of Medical Biomedical and Applied Sciences, 2018)
In recent years, there have been an increased number of reports in the literatures on animal behavioural changeslinked with intracellular protozoan Toxoplasma gondii. Evidence for animal behavioural changes with Toxoplasmagondii infection comes from experimental tests on animal models such as mice and rats. These studies describethe important mechanisms of behavioural changes which involving neuromodulator and neurotransmitter level.Furthermore, behavioural changes also have been identified in human as well as animal models that may also playa role in development of schizophrenia in humans